Meningkatkan Brand Image melalui Kualitas Produk dan Gaya Hidup Hedonis - Sarimaryoni, Hamdi; Darodjatun, M.A.S Sridjoko; Prambudi, Bono; Imron, Moch; Huda, Nurul; Mubais, Ahmad (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2024)
This study aims to analyze the influence of Product Quality and Hedonic Lifestyle on the Brand Image of Wuling-branded vehicles in the Jepara region. The research employs a survey method with an accidental sampling technique, involving 100 respondents. Data collected includes both primary and secondary sources, analyzed using multiple linear regression. The findings reveal that an improvement in product quality significantly contributes to Wuling's brand image, with a regression coefficient of 0.386, indicating that a 1% increase in product quality enhances the brand image by 0.386%. Additionally, hedonic lifestyle positively impacts brand image, with a coefficient of 0.210. These results underline the importance of product quality and engaging marketing strategies in attracting consumer interest. The uniqueness of this research lies in its focus on the interaction between product quality and hedonic lifestyle within the context of the automotive market in Jepara, a topic rarely explored in existing literature. This study provides new insights for Wuling manufacturers to formulate more effective marketing strategies while emphasizing continuous attention to product quality to maintain customer loyalty in a competitive market. Consequently, this research not only contributes to marketing theory development but also offers practical implications for Indonesia's automotive industry.